e-Punch Card: A solution for human resource issues / Razulaimi Razali, Khairul Nizam Abd Halim and Mohd Norafizal Abdul Aziz - Razali, Razulaimi; Abd Halim, Khairul Nizam; Abdul Aziz, Mohd Norafizal (2006)
Attendance is one of the most important data that will be tracked and monitored by an organisation. The data will show part of the activities and the availability of the staff in the office. In Malaysia, there are a lot of methods being applied to fulfill that purpose. Some of the methods are attendance sheet, attendance book, punch card system and others. This paper will concentrate on the usage of punch card system in Universiti Teknologi MARA (UiTM) Pahang. The issues discussed are related to the advantages, disadvantages and management of the punch card system. This paper will also identify the current issues and problems on the usage of the punch card system in the context of the staff and the management. Findings from the research show that the management should implement a new system for improvement and implementing an e-Punch Card System is an ultimate solution to resolve the issue. Furthermore, this paper will detail out the advantages of the solution and preparation on the organisation on accepting the solution. The solution for the improvement will give positive impact to the management especially toward becoming a world class university.